1993
DOI: 10.1159/000236452
|View full text |Cite
|
Sign up to set email alerts
|

Suramin Affects Human Peripheral Blood Mononuclear Cells in vitro: Inhibition of T Cell Growth and Modulation of Cytokine Secretion

Abstract: Suramin, a polyanionic compound, which has been in clinical use for the treatment of African trypanosomiasis for several decades, has recently been introduced in clinical oncology. Its effects on the immune system seemed therefore of interest. In the present study we tried to elucidate in vitro how suramin affected different functions of human peripheral blood mononuclear cells (PBMC). Suramin suppressed the proliferation of PBMC in response to various stimuli, including OKT3, phytohemagglutinin (PHA), phorbol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…However, competitive inhibition of growth factors is not the only mode of action for suramin. Suramin also acts by inhibiting intracellular secondary messengers and many intranuclear enzymes and it is speculated to have immunosuppressive properties that suppress inflammation following tissue damage [32] . We have also previously shown that, similar to MMC, suramin causes fibrosis, decreased collagen-III deposition, decreased infiltration of T lymphocytes and, to a lesser extent, of macrophages and B lymphocytes [20] .…”
Section: Discussionmentioning
confidence: 99%
“…However, competitive inhibition of growth factors is not the only mode of action for suramin. Suramin also acts by inhibiting intracellular secondary messengers and many intranuclear enzymes and it is speculated to have immunosuppressive properties that suppress inflammation following tissue damage [32] . We have also previously shown that, similar to MMC, suramin causes fibrosis, decreased collagen-III deposition, decreased infiltration of T lymphocytes and, to a lesser extent, of macrophages and B lymphocytes [20] .…”
Section: Discussionmentioning
confidence: 99%